2004
DOI: 10.1191/0960327104ht428oa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipoic acid on the oxidoreductive status of red blood cells in rats subject to oxidative stress by chronic administration of adriamycin

Abstract: One of the most intriguing phenomena observed during adriamycin (ADR) toxicity has been attributed to ADR-induced oxidative stress. The study was aimed to assess the protective effect of lipoic acid (LA) against ADR induced damage to erythrocytes. Male albino rats (Wistar strain) were subjected to ADR (1 mg/kg body weight/day i.v.) once a week for a period of 12 weeks. Haematological indices like haemoglobin levels (Hb) and haematocrit (Ht) were also lowered along with a marked increase in the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…An additional benefi cial effect of ␣ -lipoic acid on the heart was already reported in rats exposed to adriamycin [28,29] . A similar protective mechanism was observed in erythrocytes [30] and the kidney [31] .…”
Section: Discussionsupporting
confidence: 58%
“…An additional benefi cial effect of ␣ -lipoic acid on the heart was already reported in rats exposed to adriamycin [28,29] . A similar protective mechanism was observed in erythrocytes [30] and the kidney [31] .…”
Section: Discussionsupporting
confidence: 58%
“…Our results show after ALA supplementation OS levels were reduced, which support other studies [57][58][59][60].…”
Section: Panda Et Alsupporting
confidence: 93%
“…The decreased levels of these antioxidants in the diabetic control group was also an indication of increased oxidative stress in these kidneys. ALA improved the anti-oxidation ability in rats by regenerating vitamin C, vitamin E and SOD through an O-GlcNAc-dependent mechanism [12,14]. In this study, we found a decreased level of SOD in the diabetes control group which was possibly as a result of decreased anti-oxidation capabilities.…”
Section: Discussionmentioning
confidence: 48%
“…ALA quenches singlet oxygen, hydroxyl radicals, hypochloric acid, superoxide anion radicals, peroxyl radicals and hydrogen peroxide. ALA has metal-chelating activity and it is able to regenerate other natural antioxidants, such as vitamin C or vitamin E from their radical or inactive forms [13,14]. In light of the antioxidant activity of ALA, the purpose of this study was to verify oxidative stress in the pathogenesis of diabetic nephropathy in type 2 diabetic rats and to evaluate the protective effect of ALA on diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%